Tuning of paroxetine 3D-printable formulations for fused deposition modelling - Figueiredo, Sara (2021)
This work reports the preliminary development of paroxetine-containing formulations amenable to hot-melt extrusion coupled to fused deposition modelling-based 3D printing. Polymeric matrices were used alone, or added with processing enhancers (e.g., plasticizer and filler). The polymeric formulation containing paroxetine (30% w/w), hydroxypropylcellulose (54% w/w) and excipients (16% w/w of dicalcium dihydrate phosphate, magnesium stearate and triethylcitrate; 10:1:5 ratio) exhibited the most suitable behaviour to be extruded and 3D printed, proving that adjuvants are critical to ensure processing of the formulations.